Effect of High-Pressure Processing on the Quality of Beef and Buffalo Meat - Jaelan, Nur Hana Ahmad; Kumar, Pavan; Sazili, Awis Qurni; Ismail Fitry, Mohammad Rashedi (Journal of Meat Science, 2025)
The present study evaluated the physicochemical and textural attributes of fresh beef and buffalo meats with applied high-pressure processing. Both types of meat were pressurised at 300 and 600 MPa at 20 for 2 min and compared to the untreated samples as the control. The pH values, water holding capacity (WHC), moisture content, cooking loss, yield, colour, Warner-Bratzler shear force (WBSF), and texture profile analysis were examined. The increase in pressure showed a significant (p